2017
DOI: 10.1111/ijd.13607
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind, placebo‐controlled trial to determine the efficacy and safety of lactoferrin with vitamin E and zinc as an oral therapy for mild to moderate acne vulgaris

Abstract: Lactoferrin is an iron-binding milk-derived protein that has shown antibacterial and anti-inflammatory effects in vitro and in vivo. The objective of this study was to determine the efficacy and safety of lactoferrin, combined with vitamin E and zinc, for mild to moderate acne vulgaris. In this randomized, double-blind, placebo-controlled trial, 168 subjects aged 13-40 years old were randomly assigned to take either a capsule formulation containing lactoferrin with vitamin E and zinc or placebo twice a day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…In the analysis of female subjects, changes in the scores of moisture showed significant trend, and were significantly greater in the 200 mg and 600 mg groups, and changes in the scores of texture were also significantly greater in the 600 mg group than in the placebo group. In a previous trial, the effects of LF on acne vulgaris were more clearly observed in women, and an association with the menstrual cycle was suggested 2. This may also be relevant to the results in the present trial.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the analysis of female subjects, changes in the scores of moisture showed significant trend, and were significantly greater in the 200 mg and 600 mg groups, and changes in the scores of texture were also significantly greater in the 600 mg group than in the placebo group. In a previous trial, the effects of LF on acne vulgaris were more clearly observed in women, and an association with the menstrual cycle was suggested 2. This may also be relevant to the results in the present trial.…”
Section: Discussionsupporting
confidence: 81%
“…In previous clinical trials, the effects of LF on skin illnesses were reported;2,7,9,12,13,16 however, this is the first report suggesting the positive effects of LF on skin conditions in health subjects.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In summary, Mueller 4 and Han 14 showed lactoferrin can significantly reduced acne lesions in people with mild to moderate acne vulgaris. However, the exact anti‐inflammatory mechanism of LF in inflammatory skin diseases remains unclear.…”
Section: Discussionmentioning
confidence: 91%
“…The efficacy of oral intake of capsule formulations containing lactoferrin, zinc and vitamin E has been confirmed for mild‐to‐moderate acne vulgaris .…”
Section: Functionality Spectrum Of Zn Compoundsmentioning
confidence: 95%